Alexander the Great and the mystery of the elephant medallions - Holt, Frank L. (Hellenistic culture and society, 2003)
To all those who witnessed his extraordinary conquests, from Albania to India, Alexander the Great appeared invincible. How Alexander himself promoted this appearance is the subject of this book